Synthesis, Characterization, and Remedial Action of Biogenic p-Ag Nanoparticles - Sinha, Somya; Sibuh, Belay Zeleke; Mishra, Abhilasha; Pant, Kumud; Tomar, Shikha; Anand, Jigisha; Gupta, Piyush Kumar (Nanofabrication, 2022)
In the present study, the silver (Ag) nanoparticles (NPs) were fabricated using pakhoi (p), a traditional alcoholic beverage popularly used in the Garhwal region of Uttarakhand that has been known to possess significant antimicrobial activity properties. Different physicochemical techniques were used to characterize p-Ag NPs. The results confirm the synthesis of crystalline p-Ag NPs having a nearly spherical shape with a net positive charge. Further, p-Ag NPs exhibit strong antibacterial activity against Gram -ve bacteria. Moreover, a detailed study will be beneficial to understanding and exploiting the biomedical application and environmental remediation activity of the p-Ag NPs.